2003
DOI: 10.2355/isijinternational.43.1807
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Product of VN in Austenite of High Cr Heat Resistant Steel

Abstract: Dissolved V in austenite of 7%Cr-0.4%V-0.09%N steel (hereinafter, % means mass%) was measured and the solubility product of VN was determined as follows:where T is the absolute temperature in K. The solubility product obtained is 3 to 5 times larger than those in the literature and about one order larger than that for iron. The decrease in the activity coefficient of nitrogen due to the presence of Cr and V in the experimental steel is responsible for the increase in the solubility product of VN.KEY WORDS: pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Similar dips were observed by simply tempering the high-chromium martensitic steels. [26,27,56,57] A similar dip was also reported accompanying the recrystallization process of cold-rolled lowcarbon ferritic steel. [58] Before and after the occurrence of a dip, individual compounds or a combination of compounds of M 23 C 6 , Cr 2 N, MX, and VX were dissolved temporarily followed by reprecipitation.…”
Section: A Dip In Extracted Residuesupporting
confidence: 60%
See 2 more Smart Citations
“…Similar dips were observed by simply tempering the high-chromium martensitic steels. [26,27,56,57] A similar dip was also reported accompanying the recrystallization process of cold-rolled lowcarbon ferritic steel. [58] Before and after the occurrence of a dip, individual compounds or a combination of compounds of M 23 C 6 , Cr 2 N, MX, and VX were dissolved temporarily followed by reprecipitation.…”
Section: A Dip In Extracted Residuesupporting
confidence: 60%
“…A dip in a hardness recovery curve took place at a longer time as the tempering temperature decreased. [26,27,56,57] The apparent activation energies obtained using the hardness dip data roughly agreed with those for the diffusion of the interstitial elements in bcc iron, although the continuous softening occurring during tempering was, of course, controlled by the diffusion of substitutional atoms. [56] This is an explanation shown in the previous work for the occurrence of a dip in the extracted-residue-vs-time curve.…”
Section: A Dip In Extracted Residuesupporting
confidence: 51%
See 1 more Smart Citation
“…The hot rolled plate was normalized at 1 200°C followed by tempering at 740, 780 and 800°C for maximum 500 h. It was confirmed that neither any precipitate composed of V nor delta ferrite was observed after normalizing at 1 200°C. 13) A heat-treated specimen was dissolved in 6 N-HCl solution and the residues were separated using a filter with 0.2 mm pores. The dissolved V in the filtered solution is directly measured using an inductively coupled plasma atomic emission spectroscope (ICP).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed experimental procedure and the accuracy of the analyzing method are reported in the previous paper. 13) Vickers hardness number was determined under 10 kg load and optical microstructure and scanning electron microscopy were observed after etching using the Vilella's reagent. Integral breadth of a ͕110͖ diffraction peak was also measured using Cu Ka 1 characteristic X-ray.…”
Section: Methodsmentioning
confidence: 99%